Oligoprogression in Metastatic, Castrate-Resistant Prostate Cancer—Prevalence and Current Clinical Practice - Patel, Priyanka H.; Tunariu, Nina; Levine, Daniel S.; de Bono, Johann S.; Eeles, Rosalind A.; Khoo, Vincent; Murray, Julia; Parker, Christopher C.; Pathmanathan, Angela; Reid, Alison; van As, Nicholas; Tree, Alison C. (Frontiers in Oncology, 2022)
Aims Oligoprogression is poorly defined in current literature. Little is known about the natural history and significance of oligoprogression in patients with hormone-resistant prostate cancer on abiraterone or enzalutamide treatment [termed androgen receptor-targeted therapy (ARTT)]. The aim of this study was to determine the prevalence of oligoprogression, describe the characteristics of oligoprogression in a cohort of patients from a single center, and identify the number of patients potentially treatable with stereotactic body radiotherapy (SBRT). Methods Castration-resistant prostate cancer (CRPC) patients who radiologically progressed while on ARTT were included. Patients with oligoprogressive disease (OPD) (≤3 lesions) on any imaging were identified in a retrospective analysis of electronic patient records. Kaplan–Meier method and log-rank test were used to calculate progression-free and overall survival. Results A total of 102 patients with metastatic CRPC on ARTT were included. Thirty (29%) patients presented with oligoprogression (46 lesions in total); 21 (21% of total) patients had lesions suitable for SBRT. The majority of lesions were in the bone (21, 46%) or lymph nodes (15, 33%). Patients with oligoprogression while on ARTT had a significantly better prostate-specific antigen (PSA) response on commencing ARTT as compared to patients who later developed polyprogression. However, PSA doubling time immediately prior to progression did not predict OPD. Median progression-free survival to oligoprogression versus polyprogression was 16.8 vs. 11.7 months. Time to further progression after oligoprogression was 13.6 months in those treated with radiotherapy (RT) for oligoprogression vs. 5.7 months in those treated with the continuation of ARTT alone. Conclusions In this study, nearly a third of patients on ARTT for CRPC were found to have OPD. OPD patients had a better PSA response on ART and a longer duration on ARTT before developing OPD as compared to those developing polyprogressive disease (Poly-PD). The majority of patients (70%) with OPD had lesions suitable for SBRT treatment. Prospective randomized control trials are needed to establish if there is a survival benefit of SBRT in oligoprogressive prostate cancer and to determine predictive indicators.